Endocrinology concepts for diabetic retinopathy care: bridging systemic metabolic control with retinal disease management and patient education - Sidney Jones; Peter Koulen (Frontiers in Medicine, 2026)
Diabetic retinopathy (DR) is a leading cause of vision loss and a common microvascular complication of diabetes mellitus. Although diagnosis and management are typically guided by retinal findings, systemic metabolic factors—including glycemic control, diabetes duration, blood pressure, renal function, lipid status, and overall complication burden—play a central role in disease development and progression. Clinical decision-making often remains fragmented across endocrinology, primary care, and ophthalmology, contributing to variability in screening, referral, treatment selection, and patient education. This review proposes an integrated framework that applies endocrinology as a lens through which to better understand and manage diabetic retinopathy. The approach begins with a classification of systemic diabetes and metabolic disorders, then aligns these metabolically defined patient profiles with retinal diagnosis, monitoring, and stage-appropriate treatment strategies. Evidence is drawn from landmark endocrinology studies defining epidemiologic cohorts, diagnostic validation studies, and major randomized clinical trials as the basis for best practices in ophthalmological care. The goal is not only to synthesize evidence for clinicians, but also to support development of a concise patient-facing educational roadmap, presented as supplementary material , that summarizes disease progression, screening, treatment options, and anticipated next steps for patients. By integrating longitudinal endocrinology data with findings in ophthalmology, this framework may provide a strong rationale for interdisciplinary care, improve treatment outcomes, and promote more effective engagement of patients and their ophthalmologists in prevention and treatment of diabetic retinopathy.